Pengaruh hubungan tanpa status terhadap pembentukan identitas diri remaja - Sholehah, Farida Nafis (Maliki Interdisciplinary Journal, 2026)
The phenomenon of statusless relationships (HTS) has seen a significant increase among adolescents in line with the rapid advancement of social media technology. These relationships are characterized by deep emotional bonds without certainty of commitment and defined relationship status, thus risking affecting the development of adolescents' self-identity. This study aims to examine the impact of statusless relationships on the process of adolescent self-identity formation, by analyzing the contribution of social media in establishing this interaction pattern as a social norm. The methodological approach applied was a literature review of various national and international journals and related scientific publications, including sources from the UIN Malang repository. The research findings revealed that statusless relationships can cause internal conflict in adolescents, such as role ambiguity, emotional fluctuations, and difficulties in determining personal boundaries. Social media platforms also amplify unclear relationships through high frequency of digital interactions without an explicit commitment framework. The conclusion of this study emphasizes that relationship certainty and emotional literacy skills are crucial elements in supporting the formation of a harmonious adolescent self-identity in the digital era.